The effect of 5f states on the nd → 5f transition energies and spectra of americium ions. (8th October 2020) - Dala, N J; Zhong-Wen, Wu; Xiao-Bin, Ding; Lu-You, Xie; Chen-Zhong, Dong
Abstract: The spectra originating from the electric dipole transitions of nd ( n = 3 − 5) core excited states to the 5 f valence states of Am 2+ to Am 8+ ions have been calculated using the Dirac-Hartee-Fock method, which are compared with the results from the Flexible Atomic Code for the explanation of accuracy. It is found that both the M 4, 5 ( 3 d → 5 f ) and N 4, 5 ( 4 d → 5 f ) spectra of these ions consist of two peaks that are well separated in energy respectively by 202.11 eV and 49.10 eV due to strong spin-orbit interaction of the 3 d − 1 and 4 d − 1 hole state, while the O 4, 5 ( 5 d → 5 f ) spectra show a broad quasi-continuum profile.